The genesis and controls of gold mineralization south of Rehoboth, Namibia - Whitfield, Derek (Rhodes University, Faculty of Science, Department of Geology, 1991)
Gold mineralization is hosted within gossanous quartz-haematite veins in volcano-sedimentary lithologies of the Klein Aub - Rehoboth basin of the Irumide Belt, Namibia. Mineralization and hydrothermal alteration are restricted to deformed lithologies particularly the metasediments. Lithological relationships, geochemistry and metallogenic characteristics of the Irumide Belt suggest an intra-continental rift setting. Copper mineralization is well known along the length of the belt, from Klein Aub in the southwest to Ghanzi in the northeast, whereas gold mineralization appears restricted to the Klein Aub Rehoboth basin. The gold is envisaged as having being leached initially from graben fill sequences during rift closure and basin dewatering. Location of the mineralization is strongly controlled by structure and lithological contact zones. Such zones are percieved as having acted as conduit zones for escaping mineralized fluids during basin closure and deformation. Apart from the lack of an effective mineralizing trap, all features consistent with the development of an ore deposit are present. The largest mineralization traps within the area studied are shear zones followed by lithological contact zones. The Mebi and Blanks gold mines are developed over large shear zones while the Swartmodder and Neuras gold mines are situated over mineralized lithological contacts. The Swartmodder copper mine yielded ore from a mineralized schist enclave within granite. Copper and gold occurrences are attributed to two contrasting styles of mineralization. Copper mineralization is suggested to have developed during initial rifting of the belt (ie. stratabound sedimentary exhalative type), while the gold and minor copper resulted from rift closure and basin dewatering. Although no economical orebody was realized during the course of this study a model is proposed for the development of mineralization within the Irumide basement lithologies as a working hypothesis for future exploration.
Keywords: Gold ores -- Geology -- Namibia; Gold ores -- Geology -- Africa, Southern